Correlation and Causation Analysis Between COVID-19 and Environmental Factors in China - Zheng, Zuofang; Dou, Junxia; Cheng, Conglan; Gao, Hua (Frontiers in Climate, 2021)
Understanding the possible impact of meteorological and environmental conditions on the spread of COVID-19 can guide pandemic prevention and control measures. In this study, the data from 265 cities in China were analyzed. The results show that the correlation between COVID-19 and air quality index was very weak, and with meteorological factors were significantly different in different climate backgrounds. The climate background suitable for the spread of COVID-19 in China is air temperature 0-15 °C, specific humidity < 3 g·kg-1, and wind speed < 3 m·s-1. The Granger causality test shows that there is a causal relationship between the daily average air temperature and the number of COVID-19 confirmed cases in some cities in China, and air temperature is indicative of the number of confirmed cases the next day. However, this phenomenon is not universal due to regional climate differences.